Investigations on the Changes in Mineral Composition of Turkish Hazelnuts (Corylus maxima Miller) - Gulay Kirbaslar, F.; Tavman, Aydin; Turker, Artac; Turdu, Selcuk (Asian Journal of Chemistry, 2016)
Mineral composition in Turkish hazelnuts (Fosa) was investigated for consecutive six years between 1994–1999. Sodium, potassium, magnesium, calcium, phosphorus, iodine, iron, manganese, zinc, molybdenum, selenium contents of hazelnut samples were determined using atomic absorption spectroscopy and colorimetric methods. The mean contents of iron, calcium, magnesium, potassium, sodium, zinc, manganese, phosphorus, iodine, molybdenum and selenium are 4.51 ± 0.46, 127.19 ± 3.31, 175.71 ± 2.52, 568.95 ± 4.80, 2.09 ± 0.32, 2.92 ± 0.07, 9.39 ± 0.15, 270.61 ± 2.62, 4.20 ± 0.09, 0.84 ± 0.09 and 2.51 ± 0.11 mg/100 g, respectively. The differences in the analyzed mineral constituents were tested by the ANOVA statistical test.